2013
DOI: 10.1007/s12253-013-9720-3
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of CD147, MMP-2 and MMP-9 in Laryngeal Carcinoma and its Correlation with Poor Prognosis

Abstract: The objectives of this study are to investigate the expressions of matrix metalloproteinase inducing factor (CD147), matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-9 (MMP-9) in laryngeal tumor tissues and its significant correlation with tumor infiltration, metastasis and prognosis. Laryngeal tumor tissue from 48 laryngeal cancer patients with complete clinical information was collected. The laryngitis tissue from 15 patients were collected as control group. Immunohistochemical analysis for CD147… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 12 publications
3
32
0
1
Order By: Relevance
“…Patients with high CD147 expression have a poor prognosis [104], while multivariate analysis revealed that the expression of CD147 is an independent prognostic factor for patients with NSCLC [81,176]. The five-year survival rate in NSCLC cases with low CD147 expression is higher than that in cases with high expression [176], and CD147 may therefore represent a useful biomarker for prognostic evaluation.…”
Section: Clinical Applications Of Cd147mentioning
confidence: 99%
“…Patients with high CD147 expression have a poor prognosis [104], while multivariate analysis revealed that the expression of CD147 is an independent prognostic factor for patients with NSCLC [81,176]. The five-year survival rate in NSCLC cases with low CD147 expression is higher than that in cases with high expression [176], and CD147 may therefore represent a useful biomarker for prognostic evaluation.…”
Section: Clinical Applications Of Cd147mentioning
confidence: 99%
“…Cell-surface molecules preferentially expressed on LSCC compared to their normal counterparts are potential candidates of biomarker. Thus far, several molecules, including CD34, CD44, CD105, CD133 and CD147 [6][7][8][9], have been identified as favorable markers in the prediction of LSCC. In terms of the fact that it may be insufficient to predict LSCC with only single marker, more efficient ones need to be explored [5].…”
Section: Cd47 Is a Potential Target For The Treatment Of Laryngeal Sqmentioning
confidence: 99%
“…To explore the possible molecular mechanism of the contribution of anti-TNFRSF6B antibody in glioma cells, we performed western blot to determine the influence of anti-TNFRSF6B antibody on MMP-2, ERK1/2 and AKT. MMP-2 is a proteolytic enzyme that can degrade extracellular matrix components and plays an important role in tumorigenesis, invasion and metastasis of cancers [17][18][19][20][21][22][23][24] and it has been reported that in esophageal cancer tissues, TNFRSF6B expression is positively correlated to MMP-2 [19]. The activation of ERK and AKT pathways also represent the ability of survival, proliferation and apoptosis in cancers.…”
Section: Discussionmentioning
confidence: 99%